Distribution of extant xenarthrans (Mammalia: Xenarthra) in Argentina using species distribution models - Abba, Agustin Manuel (2012)
The xenarthrans are the only group of mammals that originated in South America; there are 31 living species: six sloths, four anteaters, and 21 armadillos. In Argentina, 18 species of xenarthrans were cited. The objectives of this study were to compile the existing information on the distribution of the xenarthrans of Argentina, to use species distribution models to map the potential distribution of these species, and to assess patterns of species richness of this important group of mammals. We obtained a total of 975 records corresponding to 706 different collecting localities from Argentina. We generated species distribution models for 15 of the 18 species present in the country. Virtually all of Argentina is occupied by xenarthrans. The highest richness of species is in the north and northeast of the country in the humid and arid Chaco, probably in relation with the mosaic of ecosystems recorded in these regions. These ecoregions have different degrees of habitat degradation and continues to be a major threat for the viability of the xenarthrans occurring there. The information given in this contribution is an input to clarify occurrence and distribution of this group of mammals.